Review of Black Feminism Reimagined: After Intersectionality - Abdullah, Hogar Najm (AMERICANA E-journal of American Studies in Hungary, 2021)
Black Feminism Reimagined: After Intersectionality Jennifer C. Nash Durham and London: Duke University Press, 2019 171 pages ISBN: 978-1-478-00059-4